2009
DOI: 10.1111/j.1349-7006.2008.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of 8q24/c‐MYC translocation in diffuse large B‐cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) has heterogeneous clinical, histological, and molecular features. We evaluated the clinical characteristics and prognoses of patients with DLBCL carrying 8q24 translocations. A total of 1864 consecutive patients with nonHodgkin's lymphoma were treated in the Adult Lymphoma Treatment Study Group from 1998 to 2005. Of the 252 patients with DLBCL with abnormal karyotypes, 28 patients with DLBCL with the 8q24 translocation were identified. There were 14 men and 14 women, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 19 publications
3
38
2
Order By: Relevance
“…13,34,35 Recently, the prognostic impact of chromosomal translocations involving MYC, BCL2, and BCL6 genes have been widely investigated in DLBCLs, but only a small number of studies have been conducted in the rituximab era (Table 3). 13,16,[19][20][21][22][23][24][25]35,38 In this study, the frequency of MYC rearrangement was 6%, which is comparable to the previous studies, which have reported in 3% to 16% of DLBCL. 13,18,[21][22][23][24][25][26][27] Several studies have analyzed the clinicopathologic presentations predicting the likelihood of MYC rearrangement.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…13,34,35 Recently, the prognostic impact of chromosomal translocations involving MYC, BCL2, and BCL6 genes have been widely investigated in DLBCLs, but only a small number of studies have been conducted in the rituximab era (Table 3). 13,16,[19][20][21][22][23][24][25]35,38 In this study, the frequency of MYC rearrangement was 6%, which is comparable to the previous studies, which have reported in 3% to 16% of DLBCL. 13,18,[21][22][23][24][25][26][27] Several studies have analyzed the clinicopathologic presentations predicting the likelihood of MYC rearrangement.…”
Section: Discussionsupporting
confidence: 88%
“…MYC rearrangement was significantly associated with a high proliferation rate, whereas the other studies did not show any correlation between a high proliferation rate and the presence of MYC rearrangement. [21][22][23][24] In this study, MYC-rearranged DLBCLs were more frequently found in the high-risk IPI group. Barrans and colleagues found patients with MYC-rearranged DLBCL were significantly associated with an advanced stage and a higher IPI score.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations